PERKEMBANGAN SMPN 2 SIAK HULU: Dari Awal Berdiri Hingga Menjadi Sekolah Standar Nasional (SSN) 1986-2011 - Dewi Larasati; Bedriati Ibrahim; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:. School is an institution that is both complex and unique. School as an institution of education providers that are trusted by the community as a tool to shape the personality of the individual in society, educating citizens for the better and will be expected to be useful to the nation. Schools National Standard is a manifestation of the PP 19/2005 on the National Education Standards (SNP). SMPN 2 Siak Hulu as one SSN to the quality of education in the form of aspects of input, process and output. The purpose of this study is 1) to find out what lies behind the establishment of SMPN 2 Siak Hulu in 1986, 2) to determine the role of local communities in the establishment of SMPN 2 Siak Hulu, 3) to determine the development of SMPN 2 Siak Hulu in 1986-2011, 4) to determine the efforts that have been made by principals from the beginning of the establishment to become SSN, and 5) to determine the state of SMPN 2 Siak Hulu after becoming SSN in 2011 until now. The method used is the historical method in which data were collected through library study, interview and documentation. Analysis of data using qualitative approach. When the study began filing title until the completion of a revised proposal last essay writer. The results showed that, the background of the establishment of SMPN 2 Siak Hulu because there is no school in the village of Pangkalanbaru, so that the community leaders suggested that established Junior High School in the area. The role of society in the establishment of SMPN 2 Siak Hulu is great to donate the land for the location of the establishment until reinforcements during pembangunannnya. In the development of many changes that occur in SMPN 2 Siak Hulu. The developments include the development of teachers, students, infrastructure to achievement and school accreditation. Further, each principal has their own way to promote education in SMPN 2 Siak Hulu. After SSN is set to be the year 2011, SMPN 2 Siak Hulu continue to make improvements to improve the quality of education that includes aspects of input, process and output. Based on these results it can be concluded that the developments happening in SMPN 2 Siak Hulu to promote education from its inception in 1986 until set to SSN in 2011, and until now.Key Words: Development of SMPN 2 Siak Hulu, National Standard School (SSN)